DEVELOPING A RESILIENCE DESIGN CHECKLIST FOR SCHOOL-BASED DISASTER EVACUATION CENTRES IN MALAYSIA - Hasbullah, Mohd Nasurudin; Mohd Nasir, Mohamad Rusdi; Mohamad, Junainah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Schools in Malaysia are frequently designated as temporary disaster evacuation centres during floods, landslides, and other climate-related hazards due to their accessibility and community familiarity. However, many schools were not originally designed to function as emergency shelters, resulting in challenges such as overcrowding, inadequate sanitation, limited accessibility, and insufficient space functionality. These shortcomings compromise evacuee safety, dignity, and well-being, particularly among vulnerable groups such as children, older persons, and persons with disabilities. This study aims to address these gaps by developing a Resilience Design Checklist for School-Based Disaster Evacuation Centres in Malaysia. The research adopts a qualitative approach through document analysis of national policies (NADMA, MKN, Ministry of Education, Ministry of Health) and international standards (Sphere Standards, Sendai Framework, IASC Guidelines). This is complemented by space provision assessment and content analysis using a structured questionnaire covering fifteen key design domains, including structural safety, space allocation, sanitation, accessibility, health and safety, education continuity, and sustainability. Findings reveal the absence of standardised minimum shelter design criteria and the prevalence of ad hoc adaptation of school facilities during emergencies. The proposed checklist translates international standards into a practical, context-sensitive tool that can guide assessment, retrofitting, and preparedness planning for Malaysian schools. This innovation supports Sustainable Development Goals (SDG 3, SDG 4, and SDG 11) and contributes towards building resilient, inclusive, and disaster-ready communities.